2020
DOI: 10.3892/etm.2020.8681
|View full text |Cite
|
Sign up to set email alerts
|

Differential long non‑coding RNA expression profiles in the peripheral blood and CD4+ T cells of patients with active rheumatoid arthritis

Abstract: The human transcriptome is primarily composed of long non-coding RNAs (lncRNAs), which are key regulatory molecules of multiple biological processes. In the present study, the expression profiles of lncRNAs in the peripheral blood and CD4 + T cells of patients with active rheumatoid arthritis (RA) were determined. Based on the expression profiles, 493 lncRNAs and 374 mRNAs were identified to be differentially expressed in the peripheral blood of active RA patients and healthy donors. Further verification of ln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…More interestingly, a large number of noncoding fragments were found in peripheral blood cells of patients with asthma, including natural antisense chains, pseudogenes, and differential expression of ncRNA between genes [ 14 ]. In addition, some scholars found a large number of lncRNA in CD4 + and CD8 + T cells, with phased expression [ 15 , 16 ]. At the same time, the role of miRNA in regulating innate immune responses, especially macrophages and granulocytes, has been shown to alter cell development, differentiation, and the release of inflammatory factors.…”
Section: Introductionmentioning
confidence: 99%
“…More interestingly, a large number of noncoding fragments were found in peripheral blood cells of patients with asthma, including natural antisense chains, pseudogenes, and differential expression of ncRNA between genes [ 14 ]. In addition, some scholars found a large number of lncRNA in CD4 + and CD8 + T cells, with phased expression [ 15 , 16 ]. At the same time, the role of miRNA in regulating innate immune responses, especially macrophages and granulocytes, has been shown to alter cell development, differentiation, and the release of inflammatory factors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the five lncRNAs introduced above, seven upregulated lncRNAs and two down-regulated lncRNAs were detected in peripheral blood CD4 + T cells from 12 active RA patients and eight healthy individuals using magnetic beads (Li et al, 2020a). These evidences showed that lncRNAs play important regulatory role in T cell abnormalities through corresponding mechanisms.…”
Section: Lncrnas In T Cellsmentioning
confidence: 82%
“…lncRNA was originally considered to be "junk" RNA, but in recent years research works have found that lncRNA plays an important role in many life activities such as dose compensation effect, epigenetic regulation, cell cycle regulation, and cell differentiation regulation 10,11 . In recent years, more and more lncRNAs have been found to play an important role in the occurrence and development of RA 12,13 . These lncRNAs were found to participate in the regulation of apoptosis, 14 inflammatory factor secretion, 15,16 proliferation, and migration 13 in RAFLS.…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 In recent years, more and more lncRNAs have been found to play an important role in the occurrence and development of RA. 12 , 13 These lncRNAs were found to participate in the regulation of apoptosis, 14 inflammatory factor secretion, 15 , 16 proliferation, and migration 13 in RAFLS.…”
Section: Introductionmentioning
confidence: 99%